Pengaruh Psychological Safety terhadap Kinerja Karyawan Hotel Bintang 3 dan 4 di Kota Padang - Edfi, Amelia Rahma; Rinaldi, Rinaldi (Lembaga Yasin AlSys, 2024)
This study was conducted with the aim of examining the impact of psychological safety on the performance of employees of 3 and 4 star hotels in Padang City. The research method is quantitative with purposive sampling. The sample consisted of 103 employees of 3 and 4 star hotels in Padang City. Data collection using psychological safety and employee performance scales (Individual Work Performance Questionnaire). The results showed a positive influence between psychological safety and employee performance of 7,7% (R = 0.277, R Square = 0.077, p<0.05). The level of psychological safety and employee performance on the subject is in the category of very low tendency. The study found that the higher the psychological safety experienced by the employee, the higher will be the resulting performance. The findings confirmed the importance of improving employee psychological security to improve performance.